Sojourning in disciplinary cultures : a case study of teaching writing in engineering - Mathison, Maureen A. (Utah State University Press, 2019)
"A multi-year project to develop a mechanical engineering writing curriculum that satisfied the cultural needs of both compositionists and engineers. Colleagues employed intercultural communication theory and an approach to interdisciplinary collaboration to develop useful descriptions of the process of integrating writing with engineering."--Provided by publisher